2018
DOI: 10.1111/ele.13198
|View full text |Cite
|
Sign up to set email alerts
|

Running on empty: recharge dynamics from animal movement data

Abstract: Vital rates such as survival and recruitment have always been important in the study of population and community ecology. At the individual level, physiological processes such as energetics are critical in understanding biomechanics and movement ecology and also scale up to influence food webs and trophic cascades. Although vital rates and population‐level characteristics are tied with individual‐level animal movement, most statistical models for telemetry data are not equipped to provide inference about these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 86 publications
0
40
0
Order By: Relevance
“…An interesting development in that direction is by Hooten, Scharf, and Morales (2018), who present a new approach to analyse movement data, including explicit mechanistic links to physiological dynamics, to better model decision-making and movement in heterogeneous environments. Notably, this approach can be extended to accommodate additional data such as those provided by biologgers.…”
Section: Movement Analyses In the Biologging Eramentioning
confidence: 99%
“…An interesting development in that direction is by Hooten, Scharf, and Morales (2018), who present a new approach to analyse movement data, including explicit mechanistic links to physiological dynamics, to better model decision-making and movement in heterogeneous environments. Notably, this approach can be extended to accommodate additional data such as those provided by biologgers.…”
Section: Movement Analyses In the Biologging Eramentioning
confidence: 99%
“…its lethality) prey Brown et al 2016). This variation can range from being highly dynamic, as when predator hunger elicits increased foraging activity (Hooten et al 2019), to persistent, as when aggressive behavioural types are more likely to attack prey given an encounter (e.g. Michalko & Re zucha 2018).…”
Section: Properties Of the Predatormentioning
confidence: 99%
“…In this study, we demonstrated that the interplay between memory and resource preferences is sufficient to explain the formation of animal home ranges following reintroduction to a novel environment, and thus contributing to our understanding of the space-use implications of movement behaviour. The approach utilised here could be expanded to model the interconnections between movement behaviour and energy acquisition and consumption 56 , providing a framework to quantitatively characterize the fitness, and demographic consequences of animal movement patterns, and space-use 57 .…”
Section: For a Cognitive Model Including Perception And Memory)mentioning
confidence: 99%